PENINGKATAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MERONCE MENGGUNAKAN LOOSE PART DI TAMAN KANAK-KANAK KELEDANG SAMARINDA - Sinar; Liana, Heppy; Lailatul Hidayah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
This study aims to determine the improvement of fine motor skills in children aged 5-6 years through meronce activities using loose parts at the Kindergarten in Keledang, Samarinda. The method used in this research is Classroom Action Research. Classroom Action Research is research carried out in the classroom using actions to improve the quality of the teaching and learning process in order to obtain better results. Data collection techniques include observation, interviews and documentation. The data analysis technique in this Classroom Action Research will use qualitative descriptive analysis. The research subjects were students aged 5-6 years at Keledang Kindergarten, Loa Janan Ilir District, Samarinda. To obtain valid results, research techniques are carried out using two cycle steps, and each cycle consists of four stages, namely planning, action, observation and reflection. Based on the research results, it turns out that activities to improve children's fine motor skills through loose part activities in Keledang Saminda Kindergarten appeared to have increased in the good category in cycle I reaching 61%, while in cycle II it was 83%. The meronce activity using loose parts in group B at the Keledang Kindergarten, Loa Janan Ilir District, Samarinda, is very beneficial for students, so it can be used as a method of playing and learning to improve children's fine motor skills